PROPOSED MARKETING STRATEGY FOR ROAD CONSTRUCTION HEAVY EQUIPMENT LEASING (CASE STUDY: PT BERKAH BUMI CIHERANG) - Billy Jehan, Muhammad
Infrastructure development is an integral part of national development and a driver of economic growth to be a trigger for the development of an area. As was told by Joko Widodo (Jokowi) as elected president in 2019-2024 explained that accelerating and continuing infrastructure development are important and very beneficial from various sides, both economic, social and cultural. PT Berkah Bumi Ciherang (PT BBC) is a private company owned by PT Sumber Energi Alam Mineral that engaged in the Asphalt Mixing Plant (AMP) that produces Asphalt. This research focuses only on marketing strategy and find ways to increase revenue in only heavy equipment leasing of PT BBC. From the product services provided by PT BBC, they provide heavy equipment leasing. According to the data AABI provided, the reason some AMPs went out of business from year to year is because they cannot compete with local competitors and because they cannot compete with imported asphalt originating from China. The President Director said the reason is that demand for heavy equipment leasing has decreased because finding potential buyers for small companies are quite difficult. Also, the expenses are keep increasing from year to year. To propose the proper marketing strategy for PT BBC, there are two types of analyzes. First, Internal analysis that consists of Resource, STP, and marketing mix. Second, External analysis that consists of PESTEL, Porter’s 5 forces, competitor and consumer analysis. After that, SWOT and Root Cause analyzes were conducted. In this study, primary data was collected by in-depth interview to President Director who were existing and potential customers. In conducting consumer analysis, colleague recommendations are more important because trust is the most important thing for the long term. But, the current trend for some consumers is to search through the internet having a wider reach. The current condition of the construction industry has significant competition due to the opportunity to become a leader in the construction industry. With the support of the government, many businesses in the construction industry have an easier advantage to establish good cooperation with industry players. The root causes of business problems are expenses keep increased, lack of promotion, unfavorable location, and lack of performance feedback. To construct the proposed solution, TOWS matrix is done. The authors make an integrative marketing strategy based on the problems faced by PT BBC which will have a series to enforce them. There are several strategies chosen, such as optimizing word of mouth, rent a branch office in Bandung city, search engine optimization (SEO), improve PT BBC's website and registered on a construction services website.